2002
DOI: 10.1063/1.1522378
|View full text |Cite
|
Sign up to set email alerts
|

Coupling between molecular rotations and OH⋯O motions in liquid water: Theory and experiment

Abstract: A new theory is proposed to describe spectral effects of the coupling between molecular rotations and OH¯O motions in liquid water. The correlation function approach is employed together with a special type of development in which the coupling energy of these two motions is the expansion parameter. The isotropy of the liquid medium plays an essential role in this study. Based on this theory, a new infrared pump-probe experiment is described permitting a visualization of molecular rotations at subpicosecond tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
80
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(86 citation statements)
references
References 36 publications
6
80
0
Order By: Relevance
“…Here we study the temperature dependence of the dynamics of the hydrophobic hydration shells using polarization-resolved femtosecond midinfrared spectroscopy. [20][21][22][23][24][25][26][27][28][29][30] We observe that heating of the solution leads to a strong acceleration of the molecular reorientation of the hydrophobic hydration structures, which indicates that these structures become much more labile.…”
Section: Introductionmentioning
confidence: 99%
“…Here we study the temperature dependence of the dynamics of the hydrophobic hydration shells using polarization-resolved femtosecond midinfrared spectroscopy. [20][21][22][23][24][25][26][27][28][29][30] We observe that heating of the solution leads to a strong acceleration of the molecular reorientation of the hydrophobic hydration structures, which indicates that these structures become much more labile.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 The rotational signatures of water molecules have been observed for water vapor in the suband supercritical states. 11 The rotationally resolved Raman spectrum of H 2 molecules dissolved in liquid water has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17] Previous studies on pure liquid water have shown that Förster type interactions between water molecules lead to vibrational energy transfer on a time scale Ͻ100 fs. 3,5 Similar interactions have been observed for the amide vibrations of peptides 18 and for vibrations of adsorbed molecules.…”
Section: Introductionmentioning
confidence: 99%